S‐MIM field trials results. (26th February 2014) - Hermenier, Romain; Del Bianco, Alessandro; Marchitti, Maria‐Antonietta; Heyn, Thomas; Recchia, Annamaria; Collard, Florian; Andrenacci, Marco; Mendola, Gaeteno; Vaccaro, Attilio; Scalise, Sandro; De Gaudenzi, Riccardo; Arcidiacono, Antonio
SUMMARY An intelligent transport system open platform integrating the S‐band Mobile Interactive Multimedia messaging return channel protocol over satellite (based on Enhanced Spread Spectrum Aloha) has been developed and tested under real environment conditions within the framework of SafeTRIP, an FP7 EU‐funded project. This paper presents the first field trials results using the S‐band Mobile Interactive Multimedia technology. The introduced forward and return link outcomes have been derived from mobile field trials carried out in the surroundings of the German Aerospace Center (DLR) in Germany. Finally the validation of the system performances has been realized thanks to the use of a traffic emulator that can simulate a large population of Enhanced Spread Spectrum Aloha terminals. Copyright © 2014 John Wiley & Sons, Ltd.